Bacterial Isolates in Slow Resolving Pneumonias - Abdul Rasheed Qureshi, Afzaal Ullah Khan, Muhammad Irfan, Aqeel Ahmed,Khalid Farooq Bhatti, Abdul Rasheed Qureshi, Afzaal Ullah Khan, Muhammad Irfan, Aqeel Ahmed,Khalid Farooq Bhatti (Journal of Rawalpindi Medical College, 2019)
Background : To study the pattern of bacterial isolates in slow resolving pneumonia (SRP) patients Methods : In this prospective study patients (n=121) fulfilling the criteria of slow resolving pneumonia, having Age > 14 years and radiological evidence of consolidation were included in the study. Patients having Age > 65 < 14 years, not giving consent for Invasive investigation, nosocomial pneumonia, atypical pneumonia, fungal and mycobacterial infections were excluded. All patients were investigated with multiple view Chest X-ray, sputum smear for Gram staining, ZN-staining, cytology & culture sensitivity for pyogenic and fungal infections. Fiber-optic Bronchoscopy and BAL analysis was utilized. Contrast enhanced CT scan was employed for accurate definition of the lesion. Samples were sent for microbiological evaluation. Result: Age group was 14-65 years with median age 53 years. One hundred and twenty one pyogenic bacterial isolates were obtained. Gram negative bacteria were 66.11% while gram positive bacteria were 30.57 % and mixed growth were seen in 3.30%. Conclusion : Gram negative etiology predominates in SRP cases with pseudomonas at the top followed by klebsiella.